Knowledge and Perception of COVID-19 and Its Psychosocial Impact on Pre- and Post-Natal Women in Tema Metropolis, Ghana, West Africa - Adu Mensah, Derrick; Bortie, Patience Naa Adaku; Bonney, Richard Abeiku; Ashong, Sam-Kingsley; Ayamba, Emmanuel Ayimbissa; Odonkor, Stephen Tawiah (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The emergence of the coronavirus disease 2019 (COVID-19) pandemic incited series of societal changes. Adopted practices to mitigate the virus’ spread included; limiting human contact, closure of workplaces, lockdown of cities, and thus limiting health care delivery to emergency services with interruption to routine visits— such as antenatal and postnatal care. During the onset of the pandemic there was a myriad of information on the virus, with several misconceptions involving the viral infection. This study was aimed at assessing the knowledge and perceptions of COVID-19, as well as its psychosocial impact among pregnant and postnatal women in the Tema Metropolis. Subjects and Method: This cross-sectional survey was conducted among a total of 349 pregnant and postnatal women at the Tema General Hospital, Ghana. The dependent variable was outcome of a number of correct/incorrect responses given and the test scores. The independent variables were level of knowledge on COVID-19, prevention practices of COVID-19, and the psychosocial impact of COVID-19. Structured questionnaires were administered to participants to retrieve demographic information, knowledge, perception, and psychosocial impact of COVID-19 on participants. The data collected were imported into Microsoft Excel and analyzed with SPSS version 20. Data was presented as frequencies, percentages, and chi-square values. Results: The study comprised of 295 (84.5%) pregnant and 54 (15.5%) postnatal women. Generally, 80.5% of the participants had good knowledge about COVID-19, whereas 2.6% exhibited poor knowledge. Most postnatal women had the right perceptions about COVID-19, with statistical significance (p<0.050) observed among all variables. With the preventive measures, significant associations amongst both pregnant and postnatal women were observed in monitoring body temperature (OR= 0.08; 95% CI= 0.01 to 0.02; p=0.002) and seeking medical advice when ill (OR= 0.83; 95% CI= 0.01 to 0.02; p= 0.004). Based on depression anxiety score, each variable recorded a postnatal woman experiencing extremely severe psychological impact because of COVID-19, whereas only one pregnant woman experienced same. Conclusion: There were adequate knowledge about COVID-19 among both pre- and post-natal women in the study area, and very few were impacted psychologically as a result of COVID-19. Keywords: COVID-19, prenatal, postnatal, psychological, pregnant women. Correspondence: Derrick Adu Mensah, Department of Clinical Microbiology, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana/Kumasi Center for Collaborative Research in Tropical Medicine, KCCR, Kumasi, Ghana. Mobile: +2332-6168-6052. Email: derrickadumensah@yahoo.com